Effect of levels and times of foliar application of Nano fertilizer Super micro plus on concentration of some micronutrients in dry matter and yield of Rice (Oriza sativa L.) . - Jassim, Raheem .A .H . (Journal of Kerbala for Agricultural Sciences, 2018)
A field experiment was conducted in Al – Najaf Governorate during summer season 2017 to study the effect of foliar application of Nano fertilizer with three levels ( 0 & 1 & 2) gmL-1 and times application at ( tillering stage , booting stage , flowering stage ) on concentration of Fe , Zn , Cu , Mn and yield of rice (Oriza sativa L.) Amber 33 variety . according to RCBD with three replicates was designed . results showed Superior the level 2g L-1 Nano fertilizer on concentration of iron , zinc , copper and manganese in plant ( 104.56 & 23.02 &16.67 & 60.23 ) mg kg-1 dry matter and grain yield ( 5.40 Mega gm h-1 ) .Superior time of adding Nano fertilizer on flowering stage in concentration of iron and manganese in plant ( 94.11 & 53.18 ) mg kg-1 dry matter .Superior the inter action between levels and times of foliar application on concentration of iron , zinc , manganese and copper in plant in level 2g L-1 and flowering stage ( 109 & 23.7 & 61.63 & 17 ) mg kg-1 dry matter and grain yield ( 5.47 Mega gm h-1 ).